P427 SUPPLeX: appearance and performance-enhancing supplements use in people on pre-exposure ProphyLaXis. (14th July 2019) - Nhean, Salin; Tseng, Alice; Sheehan, Nancy; Bogoch, Isaac
Abstract : Background: Men-who-have-sex-with-men (MSM) may experience more body image dissatisfaction compared to heterosexual men. The desire to be muscular has been linked with use of appearance- and performance-enhancing supplements (APES), including muscle-building supplements, steroids, and fat-burning products. APES use has been associated with potential health risks including serious liver and renal abnormalities. The purpose of this study was to describe the use and safety of APES among people attending an ambulatory pre-exposure prophylaxis (PrEP) clinic. Methods: All participants ≥ 18 years on tenofovir disoproxil fumarate/emtricitabine were included; pregnant subjects were excluded. Prospective cross-sectional survey was conducted between February 1, 2018 and September 30, 2018 to assess APES usage, and retrospective chart reviews were done to determine the rates of liver and renal abnormalities from January 1, 2016 to September 30, 2018. RUCAM and Naranjo scales were used to assess causality with liver and renal abnormalities, respectively. Results: Among 50 participants (median 32 years, 52% Caucasian, 86% MSM), 72% reported lifetime APES use and 52% with recent (within the past 6 months) use (APES group). Only 28% had never used APES (non-APES group). APES and non-APES groups had similar rates of liver abnormalities (mostly Grade 1), but 2 (8%) APES participants experienced Grade 3-4 elevations compared to none in the non-APES group. Liver enzyme elevations were possibly associated with creatine (n=4), whey protein (n=3), steroids (n=2), and weight-loss supplements (n=2). In the APES group, 12% had elevated serum creatinine (all stage 1) compared to none in the non-APES group. Whey protein (n=2), creatine (n=1), steroids (n=1), and tenofovir disoproxil fumarate (n=1) were possibly associated with renal abnormalities. Conclusion: APES usage among people on PrEP was high and possibly associated with liver and/or renal abnormalities. Increasing provider and consumer awareness of potential health risks of APES is encouraged to enhance safety. Disclosure: No significant relationships.